Gradient-Enhanced Continuum Plasticity - Voyiadjis, George Z., author 194130; Song, Yooseob, author 648984; ScienceDirect (Online service) 7722 (Amsterdam : Elsevier, 2020)
Gradient-Enhanced Continuum Plasticity provides an expansive review of gradient-enhanced continuum plasticity from the initial stage to current research trends in experimental, theoretical, computational and numerical investigations. Starting with an overview of continuum mechanics and classical plasticity, the book then delves into concise lessons covering basic principles and applications, such as outlining the use of the finite element method to solve problems with size effects, mesh sensitivity and high velocity impact loading. All major theories are explored, providing readers with a guide to understanding the various concepts of and differences between an array of gradient-enhanced continuum plasticity models.